What a Wonderful World: One Man's Attempt to Explain the Big Stuff - Marcus Chown (Faber and Faber, 2013)
Why do we breathe? What is money? How does the brain work? Why did life invent sex? Does time really exist? How does capitalism work - or not, as the case may be? Where do mountains come from? How do computers work? How did humans get to dominate the Earth? Why is there something rather than nothing? In \What a Wonderful World\, Marcus Chown, bestselling author of \Quantum Theory Cannot Hurt You\ and the \Solar System\ app, uses his vast scientific knowledge and deep understanding of extremely complex processes to answer simple questions about the workings of our everyday lives. Lucid, witty and hugely entertaining, it explains the basics of our essential existence, stopping along the way to show us why the Atlantic is widening by a thumbs\' length each year, how money permits trade to time travel why the crucial advantage humans had over Neanderthals was sewing and why we are all living in a giant hologram.